Implementation of Fatwa DSN-MUI as a Basis for Regulation in Islamic Finance in Indonesia - Judijanto, Loso; Ilhamiwati, Mega; Abdullah, Rais; Winarni, Indah; Lasmiatun, KMT (Westscience Press, 2025)
This study examines the implementation of Fatwas issued by the National Sharia Council-Indonesian Ulema Council (DSN-MUI) as a foundational regulatory framework for Islamic finance in Indonesia. Through a literature review analysis, the research explores the role of these Fatwas in shaping Sharia-compliant financial practices, their integration into regulatory frameworks, and the challenges associated with their application. Key findings highlight the dual role of DSN-MUI Fatwas as theological and regulatory tools, their contribution to ensuring Sharia compliance, and the need for standardized enforcement mechanisms. Drawing lessons from global practices, this study emphasizes the importance of institutional capacity and collaboration in enhancing the effectiveness of DSN-MUI Fatwas. These insights provide a valuable roadmap for advancing Islamic finance in Indonesia, fostering alignment between religious principles and regulatory frameworks.